TALENT MANAGEMENT IN THE DIGITAL ECONOMY ERA: CHALLENGES AND SOLUTIONS - Ary Kafin Kosasih; Almira Luthfiyanti Kosasih; Kosasih (CV. Adiba Aisha Amira, 2024)
The digital economy has brought significant changes in the global business landscape, forcing organisations to re-evaluate their approach to talent management. The review in this study used the literature method. The results identified several key challenges, including the rapid pace of technological change, the growing need for new skills, and global competition for top talent. Proposed solutions include the development of a strong learning culture, the creation of an engaging employee experience, and the adoption of a data-driven talent management strategy. The research also emphasises the importance of leveraging technologies such as artificial intelligence and data analytics in the talent management process. The conclusion shows that successful talent management in the digital economy requires a paradigm shift towards a more dynamic, adaptive and human-centred model.